2020
DOI: 10.3390/f11080836
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Decadal Forest-Cover Dynamics in the Tropical Realm: Past Trends and Policy Insights for Forest Conservation in Dry Zone of Sri Lanka

Abstract: Forest-cover change has become an important topic in global biodiversity conservation in recent decades because of the high rates of forest loss in different parts of the world, especially in the tropical region. While human interventions are the major cause, natural disasters also contribute to forest cover changes. During the past decades, several studies have been conducted to address different aspects of forest cover changes (e.g., drivers of deforestation, degradation, interventions) in different parts of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 75 publications
(84 reference statements)
0
23
0
Order By: Relevance
“…This can be done by introducing drought-tolerant crops, changing crop patterns, making minor changes during the growing season, etc., so that sustainable agriculture can continue. Sri Lanka's forest cover has decreased significantly over the past few decades [81], which could have a significant impact on the increasing severity of droughts in Sri Lanka. Furthermore, a previous study [82] showed an increasing trend of annual rainfall in Sri Lanka.…”
Section: Discussionmentioning
confidence: 99%
“…This can be done by introducing drought-tolerant crops, changing crop patterns, making minor changes during the growing season, etc., so that sustainable agriculture can continue. Sri Lanka's forest cover has decreased significantly over the past few decades [81], which could have a significant impact on the increasing severity of droughts in Sri Lanka. Furthermore, a previous study [82] showed an increasing trend of annual rainfall in Sri Lanka.…”
Section: Discussionmentioning
confidence: 99%
“…GEE has become popular as a cloud computing platform to process earth observation data due to several advantages, including flexibility, efficiency, availability, bulk downloading, ingesting, and processing capabili-ties [61]. GEE helps to extract cloud-and shadow-free images [62]. There are several past studies worldwide that have been conducted using GEE [43,44,63].…”
Section: Satellite Datamentioning
confidence: 99%
“…During the past two decades, the integrity and functions of VTCSs have been degraded significantly affecting the provision of ecosystem goods and services. For example, deterioration of micro-land use components and upstream catchment forest has had a significant impact on biotic diversity (species diversity, functional diversity and vegetation structure), abiotic heterogeneity (soil erosion and land degradation) and imbalance of water budget (soil moisture, evaporation, surface runoff), leading to a significant reduction in the capacity of supplying and regulating ES in the VTCS [87][88][89][90]. Thus, the study examined the identified causal factors and their interactive relationships [27,28] within the framework of resilience, adaptive capacity, and the vulnerability (RACV) concept [29], while incorporating exposure and sensitivity indices specific to Mahakanumulla VTCS.…”
Section: Productivity Issues Linked With Socio-ecological Properties and Restoration Challengesmentioning
confidence: 99%
“…Recent studies have shown that various factors impact the ecological productivity of the VTCSs. For instance, agricultural expansion into ecologically sensitive areas of the major VTCS zones due to demographic changes and urbanization has led to a drastic reduction in forest cover during the last two decades [8,89,90]. The degradation of the integrity and functionality of the cascade ecology has resulted in the reduction of capacity to supply ES and increased severity of droughts [6].…”
Section: Productivity Issues Linked With Socio-ecological Properties and Restoration Challengesmentioning
confidence: 99%